Community empowerment model through integrative social capacitation in the development of Bissoloro Tourism Village, Gowa Regency - Nur Riswandy Marsuki; Andi Nursida; Maemunah Maemunah (Priviet Social Sciences Journal, 2026)
The development of tourism villages in Indonesia is still dominated by programmatic and top-down approaches, which often fail to build the independence and sustainability of village communities. This study aims to formulate a community empowerment model through Integrative Social Capacitation in the development of the Bissoloro Tourism Village, Gowa Regency. This study uses a qualitative approach with a case study design, through data collection techniques in the form of participatory observation, in-depth interviews, and documentation studies involving community actors, tourism village managers, village governments, and related stakeholders. The results show that the reconstruction of sustainable tourism villages is a long-term social process involving five main stages: (1) community social mapping, (2) construction of collective identity narratives based on local potential, (3) strengthening community capacity, (4) participatory institutionalization through village institutions, and (5) transformation of community meaning towards tourism villages. This process positions the community as the main actor who not only participates technically, but is also able to interpret and manage local potential reflectively and sustainably. This study recommends the Integrative Social Capacitation approach as a community empowerment strategy that connects social, cultural, economic, and institutional dimensions within a cross-sectoral and multi-actor collaboration framework. This model contributes to the development of rural sociological studies by offering a conceptual framework for community empowerment that is adaptive and oriented towards the sustainability of tourist villages.